2008 CVM News: Avian flu - Office of Communications (Cornell University, College of Veterinary Medicine, 2008)
This news item is about: Cornell's Torres helps monitor path of avian flu virus as threat to human population grows. If a virulent strain of avian influenza ever struck the U.S. poultry industry, this country probably would fare better than many other nations due to careful biosecurity procedures in force.